Resiliensi Remaja dengan Orang Tua yang Mengalami Perceraian - Sinaga, Pasya SM; Marpaung, Winida; Hasibuan, Nur Asmaija Aisyah; Natio, Chenny Chynderella; Mirza, Rina (Lembaga Teewan Journal Solutions, 2026)
Parental divorce can have psychological impacts on adolescents, such as sadness, anger, social withdrawal, and relationship trauma. Therefore, resilience is needed to help adolescents adapt, manage stress, and recover from these conditions. This study used a qualitative approach with a case study design. The subjects were selected using purposive sampling with the criteria of adolescents aged 15-25 years whose parents had divorced. Data were collected through observation and in-depth interviews conducted with four research subjects. The results showed that some subjects experienced more severe psychological pressure, such as relationship trauma, anxiety, and thoughts of ending their lives. However, over time all four subjects were able to develop resilience in dealing with these conditions. The most prominent aspects of resilience were optimism, empathy, and self-efficacy, which helped the subjects view the future more positively and continue their lives in a better direction. This process was also supported by spiritual approaches, social support, and professional assistance. At the early stage of parental divorce, the subjects experienced difficulties in emotional regulation and impulse control; however, these abilities gradually developed through the adjustment process, enabling them to manage their emotions and recover from difficult experiences.